Desquamative Interstitial Pneumonitis and Systemic Lupus Erythematosus - Faranak Esmaeilbeigi; Stephen Juvet; David Hwang; Shikha Mittoo (Canadian Respiratory Journal)
Desquamative interstitial pneumonia (DIP) is a rare form of interstitial lung disease (ILD) commonly found among healthy smokers. ILD is a rare manifestation of systemic lupus erythematosus (SLE), and typically associated with a histopathological pattern of nonspecific interstitial pneumonia (NSIP). The present article describes an unusual case of DIP in a non-smoking patient with SLE presenting as NSIP. DIP can occur in the context of SLE in patients with a negative smoking history, and clinicians should consider lung biopsy to correctly classify ILD with unusual presentation on computed tomography scan.